EFEKTIVITAS PEMANFAATAN LABOR IPA DI SMA NEGERI 1 LUBUK ALUNG - Basthoh, El; Hayati, Najmi (STKIP Pesisir Selatan, 2019)
This study aims to describe the effectiveness of the utilization of the science laboratory of SMA Negeri 1 Lubuk Alung. The population in this study were students who had used the science lab at SMA Negeri 1 Lubuk Alung, science teacher and manager of the science laboratory with a sampling technique that is purposive sampling. Data collection was carried out through a questionnaire to determine the effectiveness of the use of science laboratories. Analysis and discussion are carried out in quantitative descriptive way. Based on the analysis of the data obtained by research findings that the utilization of the science laboratory in SMA Negeri 1 Lubuk Alung as a whole scores 78.0% which is classified as an effective category.